Hepatitis-C virus (HCV) - Suwarso, Suwarso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
A new problem on hepatitis for Indonesian is hepatitis-C virus (HCV). This infection is endemic, majority sub-clinic and progressive in chronic. Viral transmission is primarily via a parenteral route, while other routes are still in debate.Diagnostic approach should be focused on how this virus developed.KeyWords: hepatitis-C virus molecular biology Westem-blot-HCV blood transfusion epidemiology